Biomonitoring levels and trends of PAHs and synthetic musks associated with land use in urban environments - Tavera Busso, Iván (2018)
Polycyclic aromatic hydrocarbons (PAHs) are some of the most studied organic compounds in urban environments, due to their known adverse effects on human health and persistence in environmental matrices. During the last decade, new groups of organic compounds with an intensive use worldwide such as synthetic musks have been raising the interest of the scientific community given their toxicity and health effects. However, literature is still scarce in studies dealing with their concentration in the environment, especially in developing countries, where they are even more rare or non-existing at all. We employed leaves of Ligustrum lucidum to assess the concentrations of PAHs and synthetic musks in different land use areas in Cordoba city, therefore contributing with environmental information in Argentina. We found higher levels of PAHs in urban and industrial areas than in the peri-urban sampling sites, naphthalene being one of the dominant PAHs in all sampling areas. Regarding synthetic musk fragrances, polycyclic musks were the most contributing compounds and the highest levels found in industrial areas as well. A high environmental risk could be expected due to the frequent occurrence of galaxolide in addition to the high hazardous potential of phantolide, which was present in 50% of the samples. The results of the present study indicate that leaves of an urban ubiquitous tree can be used to assess the spatial behavior of both “classic” and “emerging” organic pollutants, allowing an assessment of urban air quality in areas where common air sampling devices are unavailable.